Design and Formative Validation of a Guided Discovery Learning Model Integrated with Motivation to Reasoning and Proving Tasks - Selvy Musdalifah; I Wayan Sudarsana; Sukayasa; Dasa Ismaimuza; Sutji Rochaminah; Nurhayadi (Postgraduate, University of Mataram, 2026)
This study develops and evaluates an instructional model that integrates Guided Discovery Learning with Mathematical Reasoning and Proving (MRP) Tasks to support undergraduate students’ construction of mathematical proofs in Real Analysis. The research focuses on two foundational criteria in instructional development, namely validity and practicality. Expert review involving five specialists produced high Aiken V and ICC values, indicating strong conceptual coherence, structural alignment, and reliability of judgment across components of the model. Practicality was examined through one to one evaluation, small group testing, and a field implementation involving lecturers and students. Across these stages, the model received high ratings for clarity of instructional flow, readability of tasks, feasibility of classroom enactment, and support for structured reasoning processes. The findings demonstrate that the model is both theoretically sound and operationally feasible, providing a coherent pedagogical trajectory that guides learners from exploration toward formal proof construction. This study contributes a validated instructional model and establishes a foundation for future research on its effectiveness and broader applicability in advanced mathematics learning.